Pengembangan Instrument Jumping Sideways Untuk Tes Koordinasi Pada Anak Berbasis Website - Heri -Maryono; Yohandri Yohandri (Fakultas Seni Rupa dan Desain ITB, 2023)
Identification of children’s talents in the world of sports is needed to producemaximum achievements. The talent identification program in this study focuses on acoordination test using a jumping sideways instrument. Instruments still had limitationsin measurement, data processing, and data archiving. Therefore, a website-basedjumping sideways instrument was developed. This study aims to determine the designspecifications and performance specifications of the sideways jumping instrument,which is website-based. This study is research and Development. Data collectiontechniques are carried out directly and indirectly. The result of direct measurement is thenumber of jumps, and the result of indirect measurement is the accuracy and precisionof the instrument. The first conclusion is that the performance specification consists ofa NodeMCU ESP8266, pushbuttons, an LCD, other supporting electronic components,and a website. The two design specifications consist of a proper instrument accuracy of99.6% and an accuracy of 100%.